Factors affecting milk consumption among school children in urban and rural areas of Selangor, Malaysia - Hendijani, Roozbeh Babolian; Abdul Karim, Muhammad Shahrim (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2010)
The aims of this research were to investigate the present beverage choice preference of school children and to examine the most preferred type of milk that is available in the market. As well as to determine the effect of personal and environmental factors on children’s intention to consume milk and its comparison between rural and urban area of Selangor. A total of 389 of 5th grade primary school children were selected in this study. This research was supported by social cognitive theory. Multiple linear regression, Pearson product-moment correlation, and cross-tabulation were used for forecasting the factors affecting to consumption of milk. It was found that the preferred beverages of children were: Mineral water, Milo, fruit juice, milk, yoghurt, Ribena, tea and soft drinks and it was the same amongst children in urban and rural areas. Among different types of milk, children preferred flavored milk rather than plain milk. Based on the findings, personal factors were more effective than environmental factors. To increase milk intake among children, marketers need to focus and strengthen the acceptability of milk and increase consumption by altering perception of milk advertisements. This article also profiled the children who are likely to drink milk based on personal and environmental factors in different areas.